2009
DOI: 10.3340/jkns.2009.45.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Load Sharing Mechanism Across Graft-Bone Interface in Static Cervical Locking Plate Fixation

Abstract: Objective : This study is a retrospective clinical study over more than 4 years of follow up to understand the mechanism of load sharing across the graft-bone interface in the static locking plate (SLP) fixation compared with non-locking plate (NLP). Methods : Orion locking plates and Top non-locking plates were used for SLP fixation in 29 patients and NLP fixation in 24 patients, respectively. Successful interbody fusion was estimated by dynamic X-ray films. The checking parameters were as follows : screw ang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The in vitro studies comparing static and dynamic plates are controversial because of the fusion rates observed clinically for static plates. However, a study by Han et al found that static plates promote clinical fusions by dynamizing due to screw migration through the vertebral bodies [ 20 ]. In addition to screw migration and loosening, static plates also can behave as dynamic plates via screw or plate fracture.…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro studies comparing static and dynamic plates are controversial because of the fusion rates observed clinically for static plates. However, a study by Han et al found that static plates promote clinical fusions by dynamizing due to screw migration through the vertebral bodies [ 20 ]. In addition to screw migration and loosening, static plates also can behave as dynamic plates via screw or plate fracture.…”
Section: Discussionmentioning
confidence: 99%